Self-regulated learning as a mediator in the relationship between peer learning and online learning satisfaction: a study of a private university in Malaysia - Lim, Chee Leong; Ab. Jalil, Habibah; Ma'rof, Aini Marina; Saad, Wan Zuhainis (UUM Press, 2020)
Purpose- Students’ ability to self-regulate their learning and to learn effectively with peers are indicators of success in the era of the 4th Industrial Revolution. This study investigated whether peer learning helps to influence online learning satisfaction in the presence of self-regulated learning (SRL) as a mediating variable. Methodology - The study adopted a correlational research design to examine the possibility of relationships between these variables. The sample was selected based on proportional stratified sampling method. Of the 409 respondents, only 347 were valid for data analysis, forming a usable case of 84.84%. The instrument used was an online questionnaire adapted from pre-existing reliable multi-item instruments. Structural Equation Model (SEM) analysis was used to examine the relationship between the constructs in the hypothesised model, while Bootstrapping test was applied to examine the mediation effects of SRL. Findings - From the direct effect of the SEM analysis, studentsâ€™ ability to learn with peers was found to have significantly influenced their SRL strategies, while SRL strategies were found to have a positive and statistically significant effect on online learning satisfaction. Moreover, the findings from the Bootstrapping test concurred that the influence of peer learning on online learning satisfaction was fully mediated by SRL. Significance - By understanding the mediator roles played by SRL, this study hopes to provide insights for universities and course instructors to make pedagogically informed design decisions by integrating appropriate SRL strategies in the development of blended learning courses.